Surgical intervention for chronic migraine headache: A systematic review. (June 2019) - Wormald, J.C.R.; Luck, J.; Athwal, B.; Muelhberger, T.; Mosahebi, A.
Highlights: A focus on sound systematic review methodology to present an unbiased and scientific assessment of the body of knowledge for migraine surgery. Comprehensive search strategy included a range of study types to capture all relevant reports of primary clinical research, enabling a global evaluation of the topic. A descriptive analysis allowing an overview of the likely effect of a variety of surgical interventions, with a snapshot of the rates of recurrence and adverse events. Formalised assessment of methodological quality using the GRADE approach identifies specific flaws affecting the reliability of migraine surgery research to date. Limited by a paucity of methodological quality in included studies, heterogeneous interventions, inconsistent outcome reporting and variability in baseline data, intervention data and outcome data. Abstract: Aims: Migraine is a global phenomenon, affecting more than 10% of the world's population. It is characterized by unilateral headache that may be accompanied by vomiting, nausea, photophobia and phonophobia. Some patients with chronic migraine respond to extra-cranial botulinum toxin type A injection, although the benefits observed are temporary. The rationale for surgical trigger site deactivation is to achieve lasting symptomatic improvement or permanent relief from migraine. Methods: We performed a PRISMA-compliant systematic review of clinical studies evaluating surgical intervention for migraine by searching Ovid MEDLINE and EMBASE databases from inception to June 2017. Studies were independently screened by two authors. Data were extracted on study characteristics, migraine outcomes, adverse events and recurrence. The quality of evidence was assessed using the GRADE approach. The review protocol was prospectively registered on the PROSPERO database (CRD42017068577). Results: The search strategy identified 789 articles; of them, 18 studies (4 RCTs and 14 case series) were eligible for analysis. Surgical interventions were heterogeneous and variably involved peripheral nerve decompression by myectomy or foraminotomy, nerve excision, artery resection and/or nasal surgery. All studies reported significant reductions in migraine intensity, frequency, duration and composite headache scores following surgery. Study heterogeneity precluded formal meta-analysis. Where reported, adverse event rates varied markedly between studies. The quality of included studies was consistently low or very low. Conclusion: There is insufficient evidence to support the effectiveness of any specific surgical intervention for chronic migraine, especially with regard to permanent relief; however, all included studies report improvements in key outcomes following migraine surgery. A definitive, well-powered RCT with objective surgical and patient-reported outcome measures and robust adverse event reporting is required.